The use of carinated items in the Levantine Aurignacian-Insights from layer D, Hayonim Cave, W. Galilee, Israel. - Hannah Parow-Souchon; Anna Belfer-Cohen (PLoS ONE, 2024)
A longstanding debate concerns the function of carinated elements in both, the Levantine, and European Aurignacian. The present study aims to contribute to this topic with the evaluation of the carinated assemblage from layer D in Hayonim Cave, Western Galilee, Israel, one of the type sites of the Levantine Aurignacian. An operational chain reconstruction with an attribute analysis is paired with a typological approach to the preparation and maintenance products based on artefacts defined as West European Aurignacian. The results of this study are investigated with multivariate statistics offering a methodological contribution. The data is subjected to a transformation into a distance matrix using the Gower distance and tested with the adonis-algorithm for significance. The results clearly indicate that the carinated items in Hayonim Cave did fully or partially function as cores. They are accompanied by diagnostic preparation- and- maintenance products known from the literature e.g. Thèmes bladelets. The statistical analysis indicates only a minor correlation with stratigraphy yet supports the techno-typological criteria applied for defining artefact categories (cores, debitage, tools), as well as the proposed differentiation of carinated 'core' types. The non-carinated cores in Hayonim Cave are characterised by a high variability in typology and reduction concepts. A curious similarity to the Levallois-concept is observed on some of the flake cores. It is therefore suggested that the frequent recycling of Middle Palaeolithic artefacts in the Levantine Aurignacian might have given the Aurignacian flint-knappers the opportunity to study the Levallois concept and apply an approximation of it in their own core reduction strategies. The notion that Palaeolithic flint-knappers actively observed former technological systems through the discarded artefacts directly opens up a new trajectory for the understanding of lithic reduction concept permanence. The conceptual diversification and variability in Hayonim Cave D indicate a highly dynamic period in the Levantine Upper Palaeolithic which increased the adaptive potential and promoted a rapid cultural change.